A deposition-coated physical sunscreen material and preparation method thereof
By loading titanium oxide and zinc oxide particles on sheet silica, the problems of poor transparency and poor use in practical applications of physical sunscreen agents are solved, and high transparency, high barrier and high stability are achieved, which is particularly suitable for Use for sensitive skin.
Patent Information
- Application Number
- CN202410820783.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-06-24
AI Technical Summary
In actual applications, existing physical sunscreens may have problems such as poor transparency, poor use and large particle size that may affect the skin.
By loading titanium oxide and zinc oxide particles on sheet silica, the transparency and ductility of the physical sunscreen are improved, and the stability and sunscreen effect are improved through nano-level particles.
It achieves the advantages of high transparency, high barrier, and high stability. It is especially suitable for sensitive skin and avoids the risk of particles with smaller particle size penetration into the skin.
Smart Images

Figure CN118649098B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of physical sunscreen materials, and more specifically, to a deposition-coated physical sunscreen material and a preparation method thereof. Background Art
[0002] As modern society pays more and more attention to health and beauty, sunscreen products, as an important part of daily skin care, have received widespread attention. Commonly used sunscreen products include physical sunscreens and chemical sunscreens. Chemical sunscreens mainly use other film-forming substances to form a UV-absorbing barrier on the skin surface, absorbing and neutralizing UV rays to prevent UV rays from entering the skin; common ones include benzophenone, ethylhexyl salicylate, etc. The sunscreen mechanism of physical sunscreens mainly relies on reflecting and scattering UV rays to prevent UV rays from directly contacting the skin. Common ones include titanium dioxide and zinc oxide.
[0003] While absorbing UV rays, chemical sunscreens may be absorbed by the skin and enter the blood. In addition to poor stability, they can also cause health concerns. Chemical sunscreens are also irritating and may cause contact allergies and dermatitis, making them unsuitable for use on sensitive skin.
[0004] Compared with chemical sunscreens, physical sunscreens do not change when shielding ultraviolet rays, so they have higher stability. In addition, physical sunscreens do not participate in chemical reactions during the action process, and are relatively less irritating to human skin, making them more suitable for sensitive skin. In addition, physical sunscreens are safer for the human body and the environment, and will not or will not cause much pollution to the environment.
[0005] Despite the advantages of physical sunscreens, there are still some challenges in practical application. First, because physical sunscreens mainly reflect and scatter ultraviolet rays through inorganic particles, their transparency is relatively poor and they easily form white residues on the skin surface, affecting the appearance. Second, the particle size of physical sunscreens is large, which may affect the feel of the product, such as causing greasy feeling or clogging pores.
[0006] Therefore, there is room for improvement. Summary of the invention
[0007] In order to solve the above problems, the present application provides a deposition-coated physical sunscreen material and a preparation method thereof. The present application not only improves the transparency and ductility of the physical sunscreen, but also improves its feel when used by loading titanium oxide and zinc oxide particles on flaky silica. In addition, flaky silica, as a carrier, can effectively disperse and stabilize titanium oxide and zinc oxide particles, thereby improving the stability and sunscreen effect of the physical sunscreen. The physical sunscreen provided by the present application has the advantages of high barrier, high transparency, high stability, etc., and is particularly suitable for use on sensitive skin.
[0008] In the first aspect, the present application provides a deposition-coated physical sunscreen material, which adopts the following technical scheme: a deposition-coated physical sunscreen material, comprising the following components in terms of mass percentage: 18-30% titanium dioxide, 18-30% zinc oxide, 33-43% skin feel regulator, 5-15% flaky silica, and 1-7% surface treatment agent.
[0009] Titanium dioxide (TiO2) and zinc oxide (ZnO) are commonly used physical sunscreens that achieve sunscreen effects by reflecting and scattering ultraviolet rays. However, each sunscreen has its limitations: titanium dioxide has a strong sunscreen ability but poor transparency, while zinc oxide is the opposite, with high transparency but relatively weak sunscreen ability. Therefore, the present application intends to combine the advantages of both, and mixing them has become an ideal choice. The present application proposes a strategy of loading them on a specific carrier (lamellar silicon dioxide). By evenly dispersing them on a carrier, not only can the agglomeration between sunscreens be reduced, but also the stability can be improved, while reducing the potential risks to the skin. This mixed sunscreen can work synergistically, overcome their respective shortcomings, and provide a more comprehensive sunscreen effect.
[0010] Common silicon dioxide on the market is spherical, so problems such as unstable loading and easy falling off often occur, which will affect the effect and safety of sunscreen. The present application introduces flaky silicon dioxide as a new carrier. Flaky silicon dioxide has a larger specific surface area and better stability, can effectively fix titanium dioxide and zinc oxide, reduce agglomeration, and improve the overall sunscreen effect.
[0011] In order to further improve the synergistic coordination and barrier effect of sunscreen agents, it is necessary to control the particle size of titanium dioxide and zinc oxide at the nanometer level. Nano-scale particles have a larger specific surface area and better sunscreen effect, but due to their small size, there may also be a risk of penetrating the skin.
[0012] The carrier provided in this application is a large-particle flaky silicon dioxide, which can effectively solve the problem of nano-level particles penetrating the skin. The flaky silicon dioxide can not only fix the nano-level titanium dioxide and zinc oxide, but also prevent them from penetrating the skin, further improving safety.
[0013] Even if a small amount of titanium dioxide and zinc oxide loaded on the flaky silica falls off during use, the titanium dioxide and zinc oxide will spontaneously adsorb and agglomerate with each other to form larger particles, which will not penetrate into the skin, thus ensuring safety.
[0014] In addition, the present application also uses a skin feel regulator to provide good smoothness to the powder. This feature not only reduces the heaviness and powder sticking phenomenon of the sunscreen in the formula, but also makes the sunscreen smoother and easier to spread when applied, greatly improving the convenience and comfort of use.
[0015] The present application also uses a surface treatment agent to give the physical sunscreen material excellent hydrophobicity, making it very easy to disperse the physical sunscreen material in the silicone oil phase (downstream product), which not only improves the dispersibility and stability of the sunscreen agent, but also enables the sunscreen agent to quickly form a uniform and long-lasting sunscreen film after application, further enhancing the sunscreen effect and user experience.
[0016] The physical sunscreen material provided by the present application fully retains and exerts the excellent stability and safety of physical sunscreens, and also has a strong barrier ability. Compared with chemical sunscreens, the present application has higher safety and is especially suitable for use on sensitive skin.
[0017] Preferably, the skin feel regulator may be a mixture of one or more of polymethylsilsesquioxane, polydimethylsiloxane / vinyl polydimethylsiloxane crosspolymer, vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane crosspolymer, and boron nitride.
[0018] Preferably, when the skin feel regulator is polymethylsilsesquioxane, the particle size specification is 3-5 microns.
[0019] Preferably, the surface treatment agent may be a mixture of one or more of triethoxyoctylsilane, stearic acid, and sodium stearoyl glutamate.
[0020] In a second aspect, the present application provides a method for preparing a deposition-coated physical sunscreen material, using the following technical solution:
[0021] A method for preparing a deposition-coated physical sunscreen material comprises the following steps:
[0022] Step 1: Sodium silicate and hydrochloric acid are reacted in a molar ratio of (1-5):1 to prepare flaky silicon dioxide;
[0023] Step 2: co-precipitating zinc salt and titanium salt under alkali neutralization conditions to generate a titanium-zinc composite material;
[0024] The molar ratio of the zinc salt to the titanium salt is (0.8-1.2):(0.8-1.2), and the base is neutralized to maintain the pH at 8±0.5;
[0025] Step 3: The titanium-zinc composite material is adsorbed on the flaky silicon dioxide in an electrostatic adsorption manner to obtain a composite material; Step 4: The composite material is mixed with polymethylsilsesquioxane for crystallization, filter-filtered, washed, and dried to obtain a semi-finished product; Step 5: The semi-finished product is subjected to a thin film treatment using triethoxyoctylsilane, and dried to obtain a deposited and coated physical sunscreen material.
[0026] The present application prepares flaky silicon dioxide in a specific manner, which provides good conditions for the uniform and firm loading of titanium dioxide and zinc oxide, fully guarantees the dispersibility of titanium dioxide and zinc oxide, and thus ensures the transparency of the physical sunscreen material.
[0027] Titanium dioxide (TiO2) and zinc oxide (ZnO) are co-grown under specific conditions, and through precise process control, the uniform mixing of the two and their close integration with the carrier flake silicon dioxide are achieved. This co-growth method not only retains the advantages of each, but also overcomes the photocatalytic activity of titanium dioxide and the chemical activity of zinc oxide through mutual synergy, thus obtaining a product with better performance.
[0028] During the preparation process, titanium / zinc binary oxides are deposited and coated on the surface of flaky silicon dioxide by liquid phase precipitation. This high aspect ratio flaky structure not only improves the dispersion and stability of the powder, but also helps the powder to spread evenly on the skin surface, thereby improving the sun protection effect.
[0029] In order to further enhance the performance of the product, polymethylsilsesquioxane is added. The addition of this additive brings a certain degree of smoothness to the powder, reduces the heaviness and powder sticking phenomenon in the formula, and makes the product easier to apply and spread.
[0030] Finally, through the coating treatment with triethoxyoctylsilane, a modified powder with excellent hydrophobicity was obtained. This modified powder is very easy to disperse in the silicone oil phase and can quickly form a uniform and long-lasting sunscreen film to effectively block the damage of ultraviolet rays.
[0031] By adopting the above technical solution, the photocatalytic activity of titanium dioxide and the chemical activity of zinc oxide can be effectively overcome, and a unique preparation process is adopted, so that the product has excellent long-term stability and skin feel. The skin can breathe, zero burden, and long-lasting makeup does not come off, bringing users a comfortable sun protection experience.
[0032] Preferably, in step 1, the sodium silicate and the hydrochloric acid are reacted at a temperature of 80±5° C., the rotation speed is maintained at 70±10 rpm, and the aging time is 120±10 min.
[0033] Preferably, the alkali used for the alkali neutralization includes at least one or more of potassium hydroxide, sodium hydroxide and ammonium bicarbonate.
[0034] Preferably, the alkali used for the alkali neutralization is sodium hydroxide and ammonium bicarbonate.
[0035] In actual research and development, it was found that the use of sodium hydroxide and ammonium bicarbonate for alkali neutralization can be more conducive to the growth of zinc oxide particles, making their morphology better and their generation more uniform, which is conducive to being loaded on flaky silica and can have a more sufficient synergistic effect with titanium dioxide, thereby further improving the performance of physical sunscreen materials.
[0036] Preferably, the method for preparing the titanium-zinc composite material comprises the following steps:
[0037] Step 2a: preparing the titanium salt and the zinc salt into a titanium salt solution and a zinc salt solution respectively; preparing the alkali into an alkali solution;
[0038] Step 2b: mixing the titanium salt solution and the alkaline solution until uniform to obtain solution A, and maintaining the pH of solution A at 4±0.5;
[0039] Step 2c: mixing the solution A and the zinc salt solution until uniform to obtain a solution B;
[0040] Step 2d: adjusting the pH of the solution B to 8±0.5 using the alkaline solution;
[0041] Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0042] Preferably, the calcination temperature is 750-850° C., and the calcination time is 2.5-3.5 h.
[0043] Preferably, when the alkali is sodium hydroxide and ammonium bicarbonate, the preparation method of the titanium-zinc composite material comprises the following steps:
[0044] Step 2a: preparing the titanium salt and the zinc salt into a titanium salt solution and a zinc salt solution respectively; preparing the alkali into a sodium hydroxide solution and an ammonium bicarbonate solution respectively;
[0045] Step 2b: mixing the titanium salt solution and the sodium hydroxide solution until uniform to obtain a solution A, wherein the pH of the solution A is maintained at 4±0.5;
[0046] Step 2c: mixing the solution A and the zinc salt solution until uniform to obtain a solution B;
[0047] Step 2d: adjusting the pH of the solution B to 8±0.5 using the ammonium bicarbonate solution;
[0048] Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0049] By adopting the above technical solution, the generated titanium dioxide and zinc oxide can be mixed at the nano level, evenly distributed on the flaky silicon dioxide, and interact with each other, thereby inhibiting their respective photocatalytic activities and further exerting a strong effect of blocking UVA and UVB.
[0050] Preferably, the reaction conditions of the titanium-zinc composite material and the flaky silicon dioxide in step 3 are: pH maintained at 5±0.5, temperature 75°C±3, and aging for 3 hours.
[0051] The present application is not a simple mechanical mixing, but the titanium dioxide and zinc oxide are precipitated on the lamellar silicon dioxide by electrostatic adsorption, so that the combination is more firm and the dispersion is uniform.
[0052] When preparing the flaky silicon dioxide and titanium-zinc composite material, the pH has been controlled in advance within a specific range. When the two are mixed in step 3, the pH is 5±0.5.
[0053] Preferably, the crystallization conditions of step 4 are: the temperature is controlled at 80±3° C. and the stirring time is 2±0.5 h.
[0054] Preferably, the film treatment in step 5 is specifically dry surface treatment, and the surface treatment agent is covered on the surface of the semi-finished product by atomization at a rotation speed of 700±50 rpm to perform dry modification.
[0055] Preferably, during dry modification, the stirring time is 5-20 min, and the stirred powder is kept at 100-120° C. for 1-3 h.
[0056] In summary, this application has the following beneficial effects:
[0057] 1. High transparency and high barrier properties: Titanium / zinc binary oxide is produced by in-situ self-assembly technology and monodisperse surface modification process; this technology allows titanium dioxide and zinc oxide to co-grow crystals under specific conditions, overcoming the photocatalytic activity of titanium dioxide and the chemical activity of zinc oxide. The final product has better performance and excellent transparency, which fully guarantees its strong barrier performance in the UVA and UVB ultraviolet regions;
[0058] 2. Even spreading: Liquid phase precipitation is used to deposit and coat the surface of flaky silica, and the flaky structure with high aspect ratio is used to assist the powder spreading;
[0059] 3. The addition of skin feel regulator can better bring a certain degree of smoothness to the powder, reducing the heavy feeling and powder sticking phenomenon in the formula;
[0060] 4. Use surface treatment agent for coating treatment to obtain modified powder with excellent hydrophobicity, which is very easy to disperse in silicone oil phase.
[0061] 5. The formula made with this product has excellent long-term stability and skin feel, allowing the skin to breathe, with zero burden and long-lasting makeup. Compared with chemical sunscreens, it has higher light stability and safety to the human body and the environment, and is especially suitable for sensitive skin. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is an electron microscope image of the flaky silicon dioxide obtained in Example 1.
[0063] Figure 2 This is an electron microscope image of the physical sunscreen material prepared in Example 1. Among them, the strip-shaped ones are zinc oxide, and the spherical ones are titanium dioxide.
[0064] Figure 3 Electron microscope image of the physical sunscreen material prepared in Example 1. The strip-shaped material is zinc oxide, and the spherical material is titanium dioxide. DETAILED DESCRIPTION
[0065] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0066] All products used in the following examples and comparative examples are commercially available products.
[0067] Example
[0068] Example 1
[0069] A deposition-coated physical sunscreen material comprises the following components by mass percentage: 24% titanium dioxide, 24% zinc oxide, 38% skin feel regulator, 10% flaky silicon dioxide, and 4% surface treatment agent.
[0070] The skin feel regulator is polymethylsilsesquioxane with a particle size of 3-5 microns.
[0071] The surface treatment agent is triethoxyoctylsilane.
[0072] The present application also provides a method for preparing a deposition-coated physical sunscreen material, comprising the following steps:
[0073] Step 1: Preparation of flaky silicon dioxide:
[0074] Sodium silicate and hydrochloric acid were mixed in a molar ratio of 1:1, and the mixture was kept at 80°C for reaction, with the rotation speed maintained at 70 rpm and the aging time being 120 min.
[0075] Figure 1 This is an electron microscope image of flaky silicon dioxide.
[0076] Step 2: Preparation of titanium-zinc composite material:
[0077] The titanium salt is titanium chloride, and the zinc salt is zinc chloride. The molar ratio of zinc chloride to titanium chloride is 1:1.
[0078] The bases are sodium hydroxide and ammonium bicarbonate.
[0079] The specific preparation steps include:
[0080] Step 2a: Titanium chloride and zinc chloride are respectively prepared into 1M titanium chloride solution and 1M zinc chloride solution. Sodium hydroxide and ammonium bicarbonate are respectively prepared into sodium hydroxide solution and ammonium bicarbonate solution.
[0081] Step 2b: Pour 1M sodium hydroxide solution into the reaction kettle, and then slowly drop 1M titanium chloride solution into the reaction kettle under stirring.
[0082] Then, sodium hydroxide solution was slowly added into the reaction kettle to adjust the pH to 4 to obtain solution A.
[0083] Step 2c: Slowly add 1M zinc chloride solution dropwise into the reaction kettle containing solution A, and heat to 75° C. to obtain solution B.
[0084] Step 2d: Slowly drop 1 M ammonium bicarbonate solution into the reaction kettle containing solution B under stirring until the pH reaches 8.
[0085] Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0086] Step 3: Put the titanium-zinc composite material and flaky silicon dioxide into a reaction kettle, and the titanium-zinc composite material is adsorbed on the flaky silicon dioxide in an electrostatic adsorption manner, and the pH value is 5.
[0087] The reaction conditions are: temperature 75° C., aging for 3 hours, and obtaining a composite material.
[0088] Step 4: The composite material and polymethylsilsesquioxane are mixed and crystallized. The crystallization conditions are as follows: the temperature is controlled at 80° C. and stirred for 2 hours.
[0089] Then filter press, wash and dry to obtain the semi-finished product.
[0090] Specifically, the filtration uses a plate and frame filter press to ensure that the liquid is filtered out and the material is retained.
[0091] The purpose of washing is to remove excess salt ions.
[0092] Use a blast drying oven for drying at a temperature of 130°C and a drying time of 24 hours.
[0093] Step 5: Use triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and dry it to obtain a deposited and coated physical sunscreen material.
[0094] Specifically, the film treatment is a dry surface treatment. At a rotation speed of 700 rpm, triethoxyoctylsilane is covered on the surface of the semi-finished product by atomization for dry modification. The stirring time is 15 minutes and the temperature is kept at 120° C. for 2 hours.
[0095] Use a forced air drying oven for drying at a temperature of 130°C and a drying time of 4 hours.
[0096] Figure 2 , 3 This is an electron microscope image of a physical sunscreen material. The strips are zinc oxide and the spheres are titanium dioxide.
[0097] Example 2
[0098] A deposition-coated physical sunscreen material comprises the following components by mass percentage: 18% titanium dioxide, 30% zinc oxide, 43% skin feel regulator, 8% flaky silicon dioxide, and 1% surface treatment agent.
[0099] The skin feel regulator is polymethylsilsesquioxane with a particle size of 3-5 microns.
[0100] The surface treatment agent is triethoxyoctylsilane.
[0101] The present application also provides a method for preparing a deposition-coated physical sunscreen material, comprising the following steps:
[0102] Step 1: Preparation of flaky silicon dioxide:
[0103] Sodium silicate and hydrochloric acid were mixed in a molar ratio of 5:1, and the mixture was kept at 85°C for reaction. The rotation speed was maintained at 80 rpm, and the aging time was 110 minutes.
[0104] Step 2: Preparation of titanium-zinc composite material:
[0105] The titanium salt is titanium chloride, and the zinc salt is zinc chloride. The molar ratio of zinc chloride to titanium chloride is 1.2:0.8.
[0106] The bases are sodium hydroxide and ammonium bicarbonate.
[0107] The specific preparation steps include:
[0108] Step 2a: Titanium chloride and zinc chloride are respectively prepared into 0.8M titanium chloride solution and 1.2M zinc chloride solution. Sodium hydroxide and ammonium bicarbonate are respectively prepared into sodium hydroxide solution and ammonium bicarbonate solution.
[0109] Step 2b: 1M sodium hydroxide solution is added into the reaction kettle, and then 0.8M titanium chloride solution is slowly added dropwise into the reaction kettle under stirring.
[0110] Then, sodium hydroxide solution was slowly added into the reaction kettle to adjust the pH to 4 to obtain solution A.
[0111] Step 2c: Slowly add 1.2 M zinc chloride solution dropwise into the reaction kettle containing solution A, and heat to 75° C. to obtain solution B.
[0112] Step 2d: Slowly drop 1 M ammonium bicarbonate solution into the reaction kettle containing solution B under stirring until the pH reaches 8.5.
[0113] Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0114] Step 3: Put the titanium-zinc composite material and flaky silicon dioxide into a reaction kettle, and the titanium-zinc composite material is adsorbed on the flaky silicon dioxide in an electrostatic adsorption manner, and the pH value is 4.5.
[0115] The reaction conditions are: temperature 72° C., aging for 3 hours, and obtaining a composite material.
[0116] Step 4: The composite material and polymethylsilsesquioxane are mixed and crystallized. The crystallization conditions are as follows: the temperature is controlled at 83° C. and stirred for 1.5 hours.
[0117] Then filter press, wash and dry to obtain the semi-finished product.
[0118] Specifically, the filtration uses a plate and frame filter press to ensure that the liquid is filtered out and the material is retained.
[0119] The purpose of washing is to remove excess salt ions.
[0120] Use a blast drying oven for drying at a temperature of 130°C and a drying time of 24 hours.
[0121] Step 5: Use triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and dry it to obtain a deposited and coated physical sunscreen material.
[0122] Specifically, the film treatment is a dry surface treatment. At a rotation speed of 750 rpm, triethoxyoctylsilane is covered on the surface of the semi-finished product by atomization for dry modification. The stirring time is 5 minutes and the temperature is kept at 100° C. for 3 hours.
[0123] Use a forced air drying oven for drying at a temperature of 130°C and a drying time of 4 hours.
[0124] Example 3
[0125] A deposition-coated physical sunscreen material comprises the following components by mass percentage: 30% titanium dioxide, 18% zinc oxide, 33% skin feel regulator, 12% flaky silicon dioxide, and 7% surface treatment agent.
[0126] The skin feel regulator is polymethylsilsesquioxane with a particle size of 3-5 microns.
[0127] The surface treatment agent is triethoxyoctylsilane.
[0128] The present application also provides a method for preparing a deposition-coated physical sunscreen material, comprising the following steps:
[0129] Step 1: Preparation of flaky silicon dioxide:
[0130] Sodium silicate and hydrochloric acid were mixed in a molar ratio of 2:1, and the mixture was kept at 75°C for reaction, with the rotation speed maintained at 60 rpm and the aging time being 130 min.
[0131] Step 2: Preparation of titanium-zinc composite material:
[0132] The titanium salt is titanium chloride, and the zinc salt is zinc chloride. The molar ratio of zinc chloride to titanium chloride is 0.8:1.2.
[0133] The bases are sodium hydroxide and ammonium bicarbonate.
[0134] The specific preparation steps include:
[0135] Step 2a: Titanium chloride and zinc chloride are respectively prepared into 1.2M titanium chloride solution and 0.8M zinc chloride solution. Sodium hydroxide and ammonium bicarbonate are respectively prepared into sodium hydroxide solution and ammonium bicarbonate solution.
[0136] Step 2b: 1M sodium hydroxide solution is added into the reaction kettle, and then 1.2M titanium chloride solution is slowly added dropwise into the reaction kettle under stirring.
[0137] Then, sodium hydroxide solution was slowly added into the reaction kettle to adjust the pH to 4 to obtain solution A.
[0138] Step 2c: Slowly add 0.8 M zinc chloride solution dropwise into the reaction kettle containing solution A, and heat to 75° C. to obtain solution B.
[0139] Step 2d: Slowly drop 1 M ammonium bicarbonate solution into the reaction kettle containing solution B under stirring until the pH reaches 7.5.
[0140] Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0141] Step 3: Put the titanium-zinc composite material and flaky silicon dioxide into a reaction kettle, and the titanium-zinc composite material is adsorbed on the flaky silicon dioxide in an electrostatic adsorption manner, and the pH value is 5.5.
[0142] The reaction conditions are: temperature 78° C., aging for 3 hours, and obtaining a composite material.
[0143] Step 4: The composite material and polymethylsilsesquioxane are mixed and crystallized. The crystallization conditions are as follows: the temperature is controlled at 77° C. and stirred for 2.5 hours.
[0144] Then filter press, wash and dry to obtain the semi-finished product.
[0145] Specifically, the filtration uses a plate and frame filter press to ensure that the liquid is filtered out and the material is retained.
[0146] The purpose of washing is to remove excess salt ions.
[0147] Use a blast drying oven for drying at a temperature of 130°C and a drying time of 24 hours.
[0148] Step 5: Use triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and dry it to obtain a deposited and coated physical sunscreen material.
[0149] Specifically, the film treatment is a dry surface treatment. At a rotation speed of 650 rpm, triethoxyoctylsilane is covered on the surface of the semi-finished product by atomization for dry modification. The stirring time is 20 minutes and the temperature is kept at 120° C. for 1 hour.
[0150] Use a forced air drying oven for drying at a temperature of 130°C and a drying time of 4 hours.
[0151] Example 4
[0152] A method for preparing a deposited coated physical sunscreen material, which is different from Example 1 in that the alkali used for alkali neutralization in step 2 is sodium hydroxide, and ammonium bicarbonate is not used.
[0153] Example
[0154] Comparative Example
[0155] Comparative Example 1
[0156] A deposition-coated physical sunscreen material is different from Example 1 in that the flaky silicon dioxide is replaced by commercially available spherical silicon dioxide.
[0157] A method for preparing a deposition-coated physical sunscreen material comprises the following steps:
[0158] Step 1: Preparation of titanium-zinc composite material:
[0159] The titanium salt is titanium chloride, and the zinc salt is zinc chloride. The molar ratio of zinc chloride to titanium chloride is 1:1.
[0160] The bases are sodium hydroxide and ammonium bicarbonate.
[0161] The specific preparation steps include:
[0162] Step 1a: Titanium chloride and zinc chloride are prepared into 1M titanium chloride solution and 1M zinc chloride solution, respectively. Sodium hydroxide and ammonium bicarbonate are prepared into sodium hydroxide solution and ammonium bicarbonate solution, respectively.
[0163] Step 1b: Pour 1M sodium hydroxide solution into the reaction kettle, and then slowly drop 1M titanium chloride solution into the reaction kettle under stirring.
[0164] Then, sodium hydroxide solution was slowly added into the reaction kettle to adjust the pH to 4 to obtain solution A.
[0165] Step 1c: Slowly add 1M zinc chloride solution dropwise into the reaction kettle containing solution A, and heat to 75° C. to obtain solution B.
[0166] Step 1d: Slowly drop 1 M ammonium bicarbonate solution into the reaction kettle containing solution B under stirring until the pH reaches 8.
[0167] Step 1e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0168] Step 2: Put the titanium-zinc composite material and commercially available spherical silica into a reaction kettle at a pH of 5.
[0169] The reaction conditions are: temperature 75° C., aging for 3 hours, and obtaining a composite material.
[0170] Step 3: The composite material and polymethylsilsesquioxane are mixed and crystallized. The crystallization conditions are as follows: the temperature is controlled at 80° C. and stirred for 2 hours.
[0171] Then filter press, wash and dry to obtain the semi-finished product.
[0172] Specifically, the filtration uses a plate and frame filter press to ensure that the liquid is filtered out and the material is retained.
[0173] The purpose of washing is to remove excess salt ions.
[0174] Use a blast drying oven for drying at a temperature of 130°C and a drying time of 24 hours.
[0175] Step 4: Use triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and dry it to obtain a deposited and coated physical sunscreen material.
[0176] Specifically, the film treatment is a dry surface treatment. At a rotation speed of 700 rpm, triethoxyoctylsilane is covered on the surface of the semi-finished product by atomization for dry modification. The stirring time is 15 minutes and the temperature is kept at 120° C. for 2 hours.
[0177] Use a forced air drying oven for drying at a temperature of 130°C and a drying time of 4 hours.
[0178] Comparative Example 2
[0179] A deposition-coated physical sunscreen material is different from Example 1 in that the flaky silicon dioxide is replaced by commercially available mica.
[0180] A method for preparing a deposition-coated physical sunscreen material comprises the following steps:
[0181] Step 1: Preparation of titanium-zinc composite material:
[0182] The titanium salt is titanium chloride, and the zinc salt is zinc chloride. The molar ratio of zinc chloride to titanium chloride is 1:1.
[0183] The bases are sodium hydroxide and ammonium bicarbonate.
[0184] The specific preparation steps include:
[0185] Step 1a: Titanium chloride and zinc chloride are prepared into 1M titanium chloride solution and 1M zinc chloride solution, respectively. Sodium hydroxide and ammonium bicarbonate are prepared into sodium hydroxide solution and ammonium bicarbonate solution, respectively.
[0186] Step 1b: Pour 1M sodium hydroxide solution into the reaction kettle, and then slowly drop 1M titanium chloride solution into the reaction kettle under stirring.
[0187] Then, sodium hydroxide solution was slowly added into the reaction kettle to adjust the pH to 4 to obtain solution A.
[0188] Step 1c: Slowly add 1M zinc chloride solution dropwise into the reaction kettle containing solution A, and heat to 75° C. to obtain solution B.
[0189] Step 1d: Slowly drop 1 M ammonium bicarbonate solution into the reaction kettle containing solution B under stirring until the pH reaches 8.
[0190] Step 1e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
[0191] Step 2: Put the titanium-zinc composite material and mica into a reactor with a pH of 5.
[0192] The reaction conditions are: temperature 75°C, aging for 3 hours,
[0193] Step 3: The composite material and polymethylsilsesquioxane are mixed and crystallized. The crystallization conditions are as follows: the temperature is controlled at 80° C. and stirred for 2 hours.
[0194] Then filter press, wash and dry to obtain the semi-finished product.
[0195] Specifically, the filtration uses a plate and frame filter press to ensure that the liquid is filtered out and the material is retained.
[0196] The purpose of washing is to remove excess salt ions.
[0197] Use a blast drying oven for drying at a temperature of 130°C and a drying time of 24 hours.
[0198] Step 4: Use triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and dry it to obtain a deposited and coated physical sunscreen material.
[0199] Specifically, the film treatment is a dry surface treatment. At a rotation speed of 700 rpm, triethoxyoctylsilane is covered on the surface of the semi-finished product by atomization for dry modification. The stirring time is 15 minutes and the temperature is kept at 120° C. for 2 hours.
[0200] Use a forced air drying oven for drying at a temperature of 130°C and a drying time of 4 hours.
[0201] Comparative Example 3
[0202] A method for preparing a deposition-coated physical sunscreen material, which is different from Example 1 in that sodium silicate and hydrochloric acid are mixed in a molar ratio of 10:1.
[0203] Comparative Example 4
[0204] A method for preparing a deposited coated physical sunscreen material, which is different from that of Example 1 in that: in step 2, alkali neutralization is performed to maintain the pH at 11.
[0205] Comparative Example 5
[0206] A method for preparing a deposited coated physical sunscreen material, which is different from that of Example 1 in that: in step 2, alkali neutralization is performed to maintain the pH at 5.
[0207] Comparative Example 6
[0208] A method for preparing a deposition-coated physical sunscreen material is different from that of Example 1 in that: in step 3, the titanium-zinc composite material and flaky silicon dioxide are put into a reaction kettle, and the pH value is 5.
[0209] The reaction conditions are: temperature 25° C., aging for 3 hours, and obtaining a composite material.
[0210] Performance testing
[0211] Test sample preparation:
[0212] The test sample is a sunscreen lotion, which includes the following components by mass percentage:
[0213] Phase A: 1.8% PEG-10 polydimethicone, 1% lauryl PEG-9 polydimethylsiloxyethyl polydimethicone, 6% DC345 (commercially available, containing cyclopentasiloxane and cyclohexasiloxane), 5% dicaprylyl carbonate, 5% isododecane, 35% physical sunscreen materials, 0.2% bentonite, 1% polydimethicone / vinyl polydimethicone crosspolymer, 1.5% PSQ-2000 (commercially available, containing polymethylsilsesquioxane and silica).
[0214] Phase B: 38.05% water, 3% glycerol, 0.05% disodium EDTA, 0.8% sodium chloride, 1% biosaccharide gum-2, 0.2% methylparaben.
[0215] Phase C: 0.4% phenoxyethanol.
[0216] The physical sunscreen material is any one of the physical sunscreen materials in Examples 1-4 and Comparative Examples 1-6.
[0217] The method for preparing the test sample comprises the following steps:
[0218] 1. Grind phase A evenly and heat to 78°C.
[0219] 2. Heat phase B to 78°C and stir evenly, slowly add phase A to emulsify, homogenize at low speed for 2 minutes, and stir to cool down.
[0220] 3. Cool down to 45℃, add phase C, stir evenly and filter out the material.
[0221] Test 1: Transparency
[0222] Select appropriate black and white masking paper (U.S. Leneta 8K, with varnish on the surface), apply the test sample evenly on the black and white grid area of the black and white masking paper at a dosage of 1g / grid, wait for the test sample to dry, and visually observe whether the black and white grid is covered by the test sample.
[0223] If the test sample can completely cover the black and white grid, it means that the test sample has a strong covering power and relatively low transparency. If the black and white grid is still clearly visible after the test sample is covered, it means that the test sample has a weak covering power and high transparency.
[0224] The results are recorded in Table 1.
[0225] Test 2: UV Blocking
[0226] Before testing, use a blank quartz plate to test the background curve, and then accurately weigh 0.2 mg / cm 2 Place the sample on the 3M tape surface, and then use a finger with a latex cot to quickly and evenly apply the test sample. Place the sample plate in a cool place to dry naturally for 30 minutes, and then use a UV transmittance analyzer to measure the UVA and UVB protection values, which are expressed as PA value and SPF value respectively.
[0227] The method of expressing the level of UVA protection effect is: 2≤PFA<4 is PA+; 4≤PFA less than 8 is PA++; PFA≥8 is PA+++.
[0228] The results are recorded in Table 1.
[0229] Table 1
[0230]
[0231]
[0232] According to the test data in Table 1, the physical sunscreen materials prepared in Examples 1-4 can play a good ultraviolet blocking role when applied to sunscreen lotions and have high transparency.
[0233] Comparative Examples 1-6 showed different degrees of difference from Examples 1-4 in the transparency and UV blocking tests.
[0234] Comparative Example 1 is based on Example 1, but the flaky silica is replaced with commercially available spherical silica, so that the titanium-zinc composite material cannot be loaded on the silica, and the two cannot form a synergistic effect, so the performance is low.
[0235] Comparative Example 2 is based on Example 1, but the flaky silicon dioxide is replaced with commercially available mica. Although mica also has a laminated structure, it is difficult to peel off the natural laminated structure artificially, resulting in a small specific surface area of mica, making it difficult to load the titanium-zinc composite material, and also resulting in the inability to form a synergistic effect between the two, resulting in low performance. In addition, for the cosmetics industry, the heavy metal content needs to be strictly controlled, and mica is a heavy metal, which is difficult to control.
[0236] Comparative Example 3, based on Example 1, destroys the specific reaction ratio of sodium silicate and hydrochloric acid, resulting in unsatisfactory formation of flaky silicon dioxide, small quantity and / or small specific surface area, and inability to firmly load the titanium-zinc composite material, resulting in poor performance of the physical sunscreen material.
[0237] In Comparative Example 4, based on Example 1, the alkali is excessively neutralized, resulting in the inability of the titanium-zinc composite material to form a nano-scale mixture, making it impossible to exert a synergistic effect, resulting in poor performance of the physical sunscreen material.
[0238] Comparative Example 5, based on Example 1, causes insufficient alkali neutralization, which affects the nano-level mixing of the titanium-zinc composite material and forms a mixture of particles that are too large or too small, resulting in poor performance of the physical sunscreen material and poor safety.
[0239] Comparative Example 6, based on Example 1, changed the electrostatic adsorption conditions of the titanium-zinc composite material and the flaky silicon dioxide, so that the titanium-zinc composite material could not be fully and firmly adsorbed on the flaky silicon dioxide, resulting in poor performance of the physical sunscreen material.
[0240] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A deposition-coated physical sunscreen material, characterized in that: According to mass percentage, it includes the following components: 18-30% titanium dioxide, 18-30% zinc oxide, 33-43% skin feel regulator, 5-15% flaky silicon dioxide, and 1-7% surface treatment agent; The method for preparing the deposited and coated physical sunscreen material comprises the following steps: Step 1: Sodium silicate and hydrochloric acid are reacted in a molar ratio of (1-5):1 to prepare flaky silicon dioxide; Step 2: co-precipitating zinc salt and titanium salt under alkali neutralization conditions to generate a titanium-zinc composite material; The molar ratio of the zinc salt to the titanium salt is (0.8-1.2): (0.8-1.2), and the base is neutralized to maintain the pH at 8±0.5; Step 3: The titanium-zinc composite material is adsorbed on the flaky silicon dioxide in an electrostatic adsorption manner to obtain a composite material; Step 4: the composite material is mixed with polymethylsilsesquioxane for crystallization, filtered, washed and dried to obtain a semi-finished product; Step 5: using triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and drying to obtain a deposited and coated physical sunscreen material; The reaction conditions of the titanium-zinc composite material and the flaky silicon dioxide in step 3 are: temperature 75° C.±3, and aging for 3 hours.
2. A method for preparing the deposition-coated physical sunscreen material according to claim 1, characterized in that: The following steps are involved: Step 1: Sodium silicate and hydrochloric acid are reacted in a molar ratio of (1-5):1 to prepare flaky silicon dioxide; Step 2: co-precipitating zinc salt and titanium salt under alkali neutralization conditions to generate a titanium-zinc composite material; The molar ratio of the zinc salt to the titanium salt is (0.8-1.2): (0.8-1.2), and the base is neutralized to maintain the pH at 8±0.5; Step 3: The titanium-zinc composite material is adsorbed on the flaky silicon dioxide in an electrostatic adsorption manner to obtain a composite material; Step 4: the composite material is mixed with polymethylsilsesquioxane for crystallization, filtered, washed and dried to obtain a semi-finished product; Step 5: using triethoxyoctylsilane to perform thin film treatment on the semi-finished product, and drying to obtain a deposited and coated physical sunscreen material; The reaction conditions of the titanium-zinc composite material and the flaky silicon dioxide in step 3 are: temperature 75° C.±3, and aging for 3 hours.
3. The method for preparing the deposition-coated physical sunscreen material according to claim 2, characterized in that: In the step 1, the sodium silicate and the hydrochloric acid are kept reacting at a temperature of 80±5° C., the rotation speed is maintained at 70±10 rpm, and the aging time is 120±10 min.
4. The method for preparing the deposition-coated physical sunscreen material according to claim 2, characterized in that: The alkali used for the alkali neutralization includes at least one or more of potassium hydroxide, sodium hydroxide and ammonium bicarbonate.
5. The method for preparing the deposition-coated physical sunscreen material according to claim 4, characterized in that: The alkali used in the alkali neutralization is sodium hydroxide and ammonium bicarbonate.
6. The method for preparing the deposition-coated physical sunscreen material according to claim 4, characterized in that: The preparation method of the titanium-zinc composite material comprises the following steps: Step 2a: preparing the titanium salt and the zinc salt into a titanium salt solution and a zinc salt solution respectively; preparing the alkali into an alkali solution; Step 2b: mixing the titanium salt solution and the alkaline solution until uniform to obtain solution A, and maintaining the pH of solution A at 4±0.5; Step 2c: mixing the solution A and the zinc salt solution until uniform to obtain a solution B; Step 2d: adjusting the pH of the solution B to 8±0.5 using the alkaline solution; Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
7. The method for preparing a deposition-coated physical sunscreen material according to claim 6, characterized in that: When the alkali is sodium hydroxide and ammonium bicarbonate, the preparation method of the titanium-zinc composite material comprises the following steps: Step 2a: preparing the titanium salt and the zinc salt into a titanium salt solution and a zinc salt solution respectively; preparing the alkali into a sodium hydroxide solution and an ammonium bicarbonate solution respectively; Step 2b: mixing the titanium salt solution and the sodium hydroxide solution until uniform to obtain a solution A, wherein the pH of the solution A is maintained at 4±0.5; Step 2c: mixing the solution A and the zinc salt solution until uniform to obtain a solution B; Step 2d: adjusting the pH of the solution B to 8±0.5 using the ammonium bicarbonate solution; Step 2e: filtering, washing, drying and calcining to obtain a titanium-zinc composite material.
8. The method for preparing a deposition-coated physical sunscreen material according to claim 2, characterized in that: The crystallization conditions of step 4 are as follows: the temperature is controlled at 80±3° C. and stirred for 2±0.5 h.
9. The method for preparing a deposition-coated physical sunscreen material according to claim 2, characterized in that: The film treatment in step 5 is specifically dry surface treatment, and the surface treatment agent is covered on the surface of the semi-finished product by atomization at a rotation speed of 700±50 rpm to perform dry modification.
Citation Information
Patent Citations
Cosmetic containing silica-metal oxide fine particle composite material
JP1999343222A